Design and Construction of a Lithium Bromide Water Absorption Refrigerator - Kalogirou, Soteris A.; Florides, Georgios A.; Tassou, Savvas A.; Wrobel, Louis (My University, 2001)
The objective of this work is to design and construct a lithium bromide–water (LiBr-H2O) absorption refrigerator with a nominal capacity of 1 kW. Absorption refrigerators are machines, which produce cooling by using heat energy, and have no moving parts. The various stages of design are presented including the design of the evaporator, absorber, solution heat exchanger, generator and condenser. The major problem faced during the design stage was the calculation of the heat transfer coefficient (U-value) of the various components. Single-pass vertical-tube heat exchangers have been used for the absorber and for the evaporator. The solution heat exchanger was designed as a single-pass annulus heat exchanger. The condenser and the generator were designed using horizontal tube heat exchangers. The condenser handles pure water vapour and adequate equations exist for the determination of the U-value. A pool-boiling generator has been employed and its U-value was estimated experimentally as published work on this area is limited.
Keywords: Absorption cooling; Lithium bromide